Is International or Asian Criteria-based Body Mass Index Associated with Maternal Anaemia, Low Birthweight, and Preterm Births among Thai Population? - An Observational Study (Journal of Health, Population and Nutrition, 2011)
An observational study was conducted in the four southernmost provinces of Thailand aiming at determining the effect of international or Asian criteria-based body mass index (BMI) in predicting maternal anaemia, low birthweight (LBW), and preterm births among pregnant Thai women and the change in haemoglobin (Hb) level during pregnancy. Maternal anaemia was defined as a haemoglobin (Hb) level of